KNOWLEDGE OF POSTPARTUM MOTHERS ON POSTPARTUM CARE IN HEALTHCARE CENTERS IN KEBUMEN - Rahmadhani, Wulan (Jurnal Ilmiah Kesehatan Keperawatan, 2020)
ABSTRACTMother's knowledge of complications and postpartum care in the postpartum period can help mothers successfully through this critical period such as psychological changes. This study aims to evaluate postpartum care in terms of maternal knowledge in a health center in Kebumen. Cross-sectional was carried on this study with 500 postpartum mothers used multistage sampling method, were taken from 5 healthcare centers in Kebumen. demographic questionnaire and questionnaire for measuring mothers knowledge made by researcher was used in this study. Multivariable regression was carried in this study with p-value <0.05. The results of 500 mothers showed that mothers with poor of knowledge was 64 (12.8%), moderate 396 (79.2%) and good 40 (8.0%). The majority of mothers have knowledge of the four public dimensions of health, breastfeeding and nutrition, contraceptive methods and moderate infant care. Knowledge about public health and contraceptive methods shows the highest and lowest level of knowledge. There was a significant relationship between knowledge with average scores and educational status, employment status and income levels which are included in demographic characteristics (p <0.05). Referring to the results of this study showed that a moderate level of maternal knowledge about postpartum, the implementation of interventions such as educational workshops and special attention must be very important in the health center